ANALISIS SOSIAL EKONOMI KONSERVASI SATWA LIAR PADA RUANG TERBUKA HIJAU DI KOTA MEDAN - Rizki Munaza; Agus Purwoko; Pindi Patana (Peronema Forestry Science Journal, 2016)
Wildlife in the world is pressured increasly as same as by human life. One of the goverment’s efforts to maintain the presence of wildlife is through conservation activities can be combined with spatial planning activities. It is called Open Green Space. One of open green space located in the city field is conservation of in-situ at the housing of cemara asri and conservation of ex-situ at the wildlife breeding university of north sumatra. It also function as means of recreation, urban physical. Social cultural, ecological, and economic value. Therefore, this study aims to determine the socio-economic characteristics of the visitors and the economic value of wildlife conservation areas and the influence of travel cost and cost of willingness to pay for level of visits per 1000 population. Result of the data analysis shows that the social-economic  characteristics based on gender, education level, income level, age group, and address are varied. While the economic value derived based on the travel cost is not significant and cost of willingness to pay is significant  to the level of visits per 1000 population. Key word: open green space, wildlife conservation, social economic analisys